2014
DOI: 10.3109/08923973.2014.895743
|View full text |Cite
|
Sign up to set email alerts
|

Cytostatic conditioning in experimental allogeneic bone marrow transplantation: Busulfan causes less early gastrointestinal toxicity but Treosulfan results in improved immune reconstitution

Abstract: Conditioning with Treo/Flu or Bu/Flu results in decreased aGVHD severity compared to TBI. Moreover, Treo/Flu was associated with improved immune reconstitution despite the early toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…In Bouazzaoui et al's study, Flu-Bu conditioning resulted in a delayed aGVHD and improved survival compared to TBI conditioning [20]. In our study, all allotransplanted mice conditioned with Bu-Cy or Flu-Bu developed lethal aGVHD with typical manifestations and histopathological changes starting from day +7.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…In Bouazzaoui et al's study, Flu-Bu conditioning resulted in a delayed aGVHD and improved survival compared to TBI conditioning [20]. In our study, all allotransplanted mice conditioned with Bu-Cy or Flu-Bu developed lethal aGVHD with typical manifestations and histopathological changes starting from day +7.…”
Section: Discussionsupporting
confidence: 53%
“…We found that increasing the dose of Cy (300 mg/kg) or decreasing the doses of Bu (80 mg/kg) and Flu (100 or 250 mg/kg) resulted in quick death or inhomogeneous survival of the mice. Recommended from previous publications [12, 20], we determined Bu (100 mg/kg)-Cy (200 mg/kg) and Flu (500 mg/kg)-Bu (100 mg/kg) to be the optimal conditioning doses. After transplantation, the syngeneic recipients did not develop clinical manifestations of aGVHD and survived more than 45 days.…”
Section: Discussionmentioning
confidence: 99%
“…Sjoo et al [9] have shown that treatment with treosulfan induces only a short production of IL-2 and had no effect on the synthesis of tumor necrosis factor-α and INF-γ as compared with busulfan. Bouazzaoui et al [33] showed in another murine model that conditioning with busulfan resulted in less tissue damage and lower expression of tumor necrosis factor-α than treosulfan; however, GVHD was not increased with treosulfan because of marked reduction of production of INF-γ Most prior clinical studies suggested a lower GVHD rate with treosulfan conditioning [4,14,19]. This is probably related to the cytokine milieu associated with treosulfan and to the limited mucositis with this regimen.…”
Section: Discussionmentioning
confidence: 99%
“…10 In contrast, allogeneic mice displayed a high pathology score in liver, lung, small intestine, colon, and skin, whereby the difference between IgY-fed animals and controls was significant for the colon only (4.07 6 0.57 vs 5.58 6 0.51; P , .05). The impact of IgY on colon pathology is expected because the colon Cytokine levels on day 28 after alloBMT.…”
Section: And Ernst Hollermentioning
confidence: 95%